(untitled) (Central Asian Journal of Medical Sciences, 2017)
Objectives: Our study determined the genetic effect of Apolipoprotein A-V (APOA5) gene polymorphisms on lipid parameters in patients with metabolic syndrome (MetS). Methods: 160 patients with MetS and 144 healthy individuals were selected for the case and control groups, respectively. APOA5 gene polymorphisms (-1131T>C, IVS3+476G>A, c.1177C>T, c.1259T>C) were genotyped using PCR-RFLP. Results: Serum levels of total cholesterol and triglyceride were higher in the MetS group than the control group (p=0.028, p<0.001), while high density lipoprotein levels was lower in the MetS group than the control group (p=0.048). The -1131C allele frequency was higher in the MetS group than the control group (p=0.048). Results of regression analysis showed that APOA5−1131C carriers had increased incidences of MetS (OR=1.87, p=0.010). The frequency of the haplotype C-A-T-C was higher in the MetS group than the control group (p=0.027). In the MetS group, the triglyceride level was significantly higher in the minor allele carriers of -1131T>C, IVS3+476G>A, c.1177C>T. Conclusion: Our results suggest that, among the APOA5 SNPs, the C allele of -1131T>C polymorphism is a risk factor for MetS.